3x+5=(x+5)*2

Simple and best practice solution for 3x+5=(x+5)*2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5=(x+5)*2 equation:



3x+5=(x+5)*2
We move all terms to the left:
3x+5-((x+5)*2)=0
We calculate terms in parentheses: -((x+5)*2), so:
(x+5)*2
We multiply parentheses
2x+10
Back to the equation:
-(2x+10)
We get rid of parentheses
3x-2x-10+5=0
We add all the numbers together, and all the variables
x-5=0
We move all terms containing x to the left, all other terms to the right
x=5

See similar equations:

| 3r+6=-12 | | 2u+1=-17 | | 2-b+1=8 | | 4e+9=33 | | 2x/3-1/4-2=x | | 10x-3=5x+32 | | 6z+2=-10 | | 12x-7=2x+83 | | 12-4(3x-2)=42-15x | | 6z+2=-2 | | (43+b)/2=30 | | 12x^2-68x=-96 | | (43+b)/2=32 | | 4h+9=49 | | x3–x=30 | | 2l+2=0 | | .6x=800 | | 3a+8=9 | | (p+840)/8=535 | | 1-x=2x+2/3 | | 2x2+13x+7=0 | | 12w-45=4w+51 | | -12x^2-88x-20=0 | | k=-4,5 | | 6x+1=3(9x+1)+12 | | 0=-3x2+6x-8 | | 2²n+¹=512 | | 6x–9=3x+12 | | 7c-28=2c+22 | | 9g+7=4g-13 | | 2x+40=12x-120 | | 4a-3a+6=4a-8 |

Equations solver categories